Race and Racism in Nineteenth-Century Art : The Ascendency of Robert Duncanson, Edward Bannister, and Edmonia Lewis - Woods, Naurice Frank, Jr (Book collections on Project MUSE., 2021)
"Painters Robert Duncanson (ca. 1821-1872) and Edward Bannister (1828-1901) and sculptor Mary Edmonia Lewis (ca. 1844-1907) each became accomplished African American artists. But as emerging art makers of color during the antebellum period, they experienced numerous incidents of racism that severely hampered their pursuits of a profession that many in the mainstream considered the highest form of social cultivation. Despite barriers imposed upon them due to their racial inheritance, these artists shared a common cause in demanding acceptance alongside their white contemporaries as capable painters and sculptors on local, regional, and international levels. Author Naurice Frank Woods Jr. provides an in-depth examination of the strategies deployed by Duncanson, Bannister, and Lewis that enabled them to not only overcome prevailing race and gender inequality, but also achieve a measure of success that eventually placed them in the top rank of nineteenth-century American art. Unfortunately, the racism that hampered these three artists throughout their careers ultimately denied them their rightful place as significant contributors to the development of American art. Dominant art historians and art critics excluded them in their accounts of the period. In this volume, Woods restores their artistic legacies and redeems their memories, introducing these significant artists to rightful, new audiences"--